Exploring the arcuate fasciculus from a clinical perspective - Shao, Zhi Ding; Gong, Yu Juan; Ren, Jing; Wang, Ji (Frontiers in Neuroscience, 2023)
In recent years, language function impairment caused by intracranial diseases has gained increasing interest, mainly due to its significant impact on the language and cognitive ability, leading to a serious decline in the quality of life of patients. Consequently, researchers aimed to clarify the quantitative degree of lesions of the arcuate fasciculus and therapeutic targets to promote nerve fiber remodeling. The arcuate fasciculus is extremely prone to damage caused by diseases such as stroke and brain tumor. Hallucinating schizophrenia, autism spectrum disorder, epilepsy, chronic fatigue syndrome, chronic tinnitus, and other diseases can also lead to changes in the fractional anisotropy value of arcuate fasciculus; however, different studies have different conclusions about how this change occurs. To obtain a better understanding, more clinical studies are required. Owing to various advancements in neuroimaging, a better understanding and identification of vital targets for restoration of neurological function are possible. The arcuate fasciculus is stratified into three substructures, each having unique neurological functions. Both diffusion tensor imaging (DTI) sequences and deterministic monitoring techniques render it possible to visually and quantitatively analyze the substructure in three parts. In this review, we examined the progress of the arcuate fasciculus and quantitative DTI technology in recent years.